Prevalência de sarcopenia avaliada através dos métodos recomendados pelo EWGSOP em idosas da área urbana e rural do noroeste do Rio Grande do Sul - Mazocco, Letícia (2017)
Brazil is among the countries that are facing a rapid aging process. This demographic transition is accompanied by a change in the morbidity and mortality pattern, characterized by an increase in the prevalence of chronic-degenerative diseases and disabilities. Sarcopenia is a syndrome with a high prevalence in the elderly population and with serious consequences for health. The aim of this research was to evaluate the prevalence of sarcopenia through the methods recommended by the EWGSOP in a convenience sample of elderly women submitted to bone densitometry and living in the urban and rural area of the northwest region of Rio Grande do Sul. The variables under investigation: sociodemographic characteristics, pathologies present in the elderly, prevalence of smoking and alcohol use, falls and fractures were collected through a specific form. Socioeconomic status was assessed through the application of a questionnaire established by the Brazilian Association of Research Companies (ABEP). To evaluate physical activity, we applied the International Physical Activity Questionnaire (IPAQ) short version. The weight and height were measured in an anthropometric scale, and after calculating the Body Mass Index (BMI). The prevalence of sarcopenia was performed through the recommendations of the EWGSOP: manual grip strength test, performed with the manual dynamometer; muscle mass evaluation, through dual-energy x-Ray absorptiometry (DXA) and physical performance were evaluated through the gait test. Were evaluated 205 elderly women with a mean age of 67.3 ± 5.9 years, the majority residing in rural areas (65.9%), aged 60-69 years (66.3%), caucasian (71.2%), with a partner (61.5%), with 4 to 8 years of schooling (47.3%), retired (92.2%), a member of the socioeconomic class C (61.0%), active (52.7%), non-smoker (73.2%), overweight (39.5%), with no history of falls (62.0%) or fractures (85.9%). With regard to diseases, 40% had dyslipidemia, 17.1% had diabetes, 63.4% had hypertension, 11.7% had coronary artery disease, 12.7% had rheumatoid arthritis and 11.7% had cancer. In the evaluated sample, 2.4% presented sarcopenia. Of all the variables evaluated, only the residence had a significant association with sarcopenia (p = 0.047), showing a higher prevalence among the elderly women in the urban environment (5.7%) when compared to rural women (0.7%). After multivariate analysis, the place of residence was independently associated with sarcopenia, showing a greater chance of sarcopenia in the urban elderly (OR = 9.561; 95% CI: 1.021-89.523).